Perception and Consumption of Processed and Packaged Dairy Products amongst Young Adults ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: Dairy has long been a significant component of the Indian diet, providing crucial nutrients. Processed and  packaged dairy goods contribute substantially to the increased consumption of such foods among consumers. Objective: To assess the frequency of consumption and perception of young adults for the processed and packaged dairy products.  Methodology: Descriptive cross-sectional design was adopted where young adults (n=100) from Delhi NCR in age  range of 18-26 years were assessed for consumption patterns and perception of dairy products namely lassi/chaach,  plain dahi/yogurt, milk-based ice cream/kulfi/milk lolly, flavored yogurt/ flavored dahi). The data was collected utilizing  a self-structured questionnaire, encompassing questions of sociodemographic details, frequency of consumption, and  perception regarding health beliefs. Data was analysed by descriptive statistics. Results: Majority (73%) of the subjects  were pursuing graduation and had budget of Rs 5000/- for additional expenses. For frequency of consumption 41%  of subjects consumed processed and packaged dairy products on daily basis. Majority (43% and 36% respectively)  were found to be satisfied for consumption of lassi/chaach, plain yogurt/dahi and flavored yogurt/flavored. Taste and  smell were found to be predominant factor for selection of dairy product. For factors that influence purchase decision  and dairy product selection, χ² =146.67 (p
Keywords: Dairy products; consumer; perception; processed; packaged